2010
DOI: 10.1007/s13197-010-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and consumer acceptance of a high fish protein puffed corn-fish snack

Abstract: Corn snack fortified with 7% fish protein powder made from saithe (Pollachius Virens) surimi was selected by expert panel from industry for consumer studies in Iran and Iceland. They hedonically screened products with 3%, 5%, 7% and 9% fish protein powder. Snack containing 9% fish protein powder (FP) had significantly lower liking for odour, texture, flavour, and overall acceptability than the other three prototypes. Snacks fortified with 3%, 5%, and 7% FP had similar sensory attributes. Therefore, snack with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
4
37
0
2
Order By: Relevance
“…Using FPP for producing formulated seafood and other food products has been investigated (Carvajal et al 2005;Musa et al 2005;Shaviklo et al 2010bShaviklo et al , 2011aShaviklo 2012). Applications of FPP as a binder in restructured meat (Chung et al 2000), as emulsifier in muscle foods (Ramirez et al 1999) and the development of value added products from FPP (Sathivel et al 2005) have been reported.…”
Section: Application Of Fpp In Convenience Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using FPP for producing formulated seafood and other food products has been investigated (Carvajal et al 2005;Musa et al 2005;Shaviklo et al 2010bShaviklo et al , 2011aShaviklo 2012). Applications of FPP as a binder in restructured meat (Chung et al 2000), as emulsifier in muscle foods (Ramirez et al 1999) and the development of value added products from FPP (Sathivel et al 2005) have been reported.…”
Section: Application Of Fpp In Convenience Foodsmentioning
confidence: 99%
“…The consumers liked the product but Iranian children favoured it more than Icelandic children. The majority of the children's parents expressed their willingness to choose this product when buying snacks (Shaviklo et al 2010b).…”
Section: Application Of Fpp In Convenience Foodsmentioning
confidence: 99%
“…The nutritional value and physicochemical properties of surimi powder make it ideal for producing formulated seafood and other food products (Park and Lin 2005). Since the 1990s, researchers have focused on the application of surimi powder in food products, including rice-fish snacks (Gogoi et al 1996), fish crackers (Huda et al 2001b), fish balls (Huda et al 2003), corn-fish snacks (Shaviklo et al 2010a), and fish cutlet mixes (Shaviklo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, desirable products characteristics of high expansion ratio and low bulk density and hardness were obtained at low feed moisture, high screw speed and medium to high barrel temperature. Extrusion of corn grits with fish flesh/ fish protein can be used to produce high-protein products that would be an option to provide nutrient snacks for consumers and to increase fish consumption (Shaviklo et al 2011a). Shaviklo et al (2011b) studied the acceptability of corn snack fortified with fish protein powder at different rates and reported that snacks fortified with 9 % fish protein powder showed significantly lower liking in respect of odour, texture, flavour and overall acceptability, whereas, snacks with 3 %, 5 % and 7 % fish powder showed similar sensory attributes with better acceptability.…”
Section: Introductionmentioning
confidence: 99%